Andisol and microcrystalline cellulose from Typha angustifolia for auramine O adsorption - Pranoto Pranoto; Venty Suryanti; Robi'atul Adawiyah (Institute of Advanced Engineering and Science, 2023)
Andisol has a large surface area, is mesoporous, and contains the active groups' silanol (Si-OH) and aluminol (Al-OH). Besides andisol, cellulose is a good adsorbent, because microcrystalline cellulose has an active hydroxyl group (OH). The number of active adsorbent groups can be enhanced by chemically modifying the surface area (increment), or adding other materials. These modifications included alkaline modified-andisol with the addition of NaOH to increase pore size, cellulose hydrolysis with HCl to increase surface area, and andisol modification with the inclusion of other materials, mainly cellulose, to increase surface area. After the adsorption process is complete, the adsorption capacity of andisol-microcrystalline cellulose (AMS) to auramine O (AO) is known. As an adsorbent for AO, the surface area of BET andisol is 25.92 m2/g and the pore diameter is 14.40 nm, while the surface area of microcrystalline cellulose and AMS adsorbent are 26.60 m2/g and 18.60 m2/g, respectively. The maximum AO adsorption conditions by AMS were at pH 7, optimum at a contact time of 5 minutes, and maximum at a concentration of 40 mg/L with an adsorbent ratio of 1:1. The adsorption kinetics and isotherm more closely followed the pseudo second-order and Langmuir isotherm with an adsorption capacity of 5.24 mg/g.